(untitled) (Research, Society and Development, 2021)
Nowadays, the aesthetics of the smile has been growing in the market, since many consider the aligned smile and white teeth as part of the desirable beauty standard. Therefore, tooth whitening is one of the most sought after procedures performed by dentists, in terms of aesthetics. Thus, the dentist must have a solid base of knowledge about it, so that they can make a clinical assessment and correct diagnosis of the dental structure, indicating the best technique in each case. To this end, a literature review was carried out on the types of tooth whitening, comparing them in terms of efficacy, in relation to color change, and in terms of sensitivity, with searches in the databases, Pubmed, Scielo and Scopus, through the Keywords: Tooth bleaching; Carbamide peroxide; Hydrogen Peroxide; Dentin Sensitivity. Studies in English, Portuguese or Spanish, published between 01/2006 and 05/2021, were considered eligible. Thus, it was noted that bleaching techniques are able to achieve the same results regarding color change, but with variation in time and indication. As for sensitivity, there is a tendency for this to be greater when using a higher concentration gel. However, there are already bleaching gels containing desensitizing substances, and/or protocols that can be used, so that it can be reduced. In addition, when the at-home whitening technique is performed, it is suggested to give preference to Carbamide Peroxide gel in the lowest concentration, since this presents a lower risk of developing tooth sensitivity and is effective, when compared to higher concentrations.